What is the appropriate timing for advance care planning according to patients and their relatives? A scoping review - Carolien Burghout; Sascha R. Bolt; Lenny M. W. Nahar-van Venrooij; Tineke J. Smilde; Carin C. D. van der Rijt; Eveline J. M. Wouters (PLoS ONE, 2026)
Background Advance care planning (ACP) is often initiated in the last phase of life. However, patients and relatives may need earlier conversations about their care preferences in the disease trajectory. Objective To synthesize empirical research on the appropriate timing of ACP from the perspective of patients and relatives. Additionally, we investigated facilitators, challenges, and triggers related to that timing. Design and method A scoping review was conducted using PubMed and CINAHL databases (up to April 2023; updated June 2025). Eligible studies focused on ACP timing from the perspectives of patients with cancer, heart or lung disease, and relatives. Two researchers independently screened papers and extracted data. Extracted data were clustered using thematic analysis. Results: In total, 29 papers were included. Both patients’ and relatives’ perspectives regarding the appropriate timing of initiating ACP varied widely and encompassed the entire continuum from healthy state, through illness, until the end of life. Timing related facilitating factors for initiating ACP were: clear information about prognosis, readiness, ACP as part of standard care, and clarity about who initiates ACP. Timing challenges were categorized as patient- (individual needs, coping, mutual protection), illness- (prognosis or illness related uncertainty) and professional-related (reluctance, time constraints). Additionally, patient-related (age, experiences in life) and trigger points in illness were identified. Conclusion The wide range of perspectives regarding appropriate timing of ACP requires a personalized approach. Clinical triggers may provide guidance, though they are not universally applicable. Professionals should timely and regularly explore patients’ preferences and readiness for initiating ACP conversations.